MERETAS GLASS CEILING: KORELASI DRAMA KOREA “QUEEN WOO” DAN TEKS 1 TIMOTIUS 2:11-12 SERTA IMPLIKASINYA TERHADAP KEPEMIMPINAN PEREMPUAN - Saputra, Jefri Andri (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2025)
This article aims to break down the hidden barriers that make it difficult for women to become leaders like men. Gender equality has provided opportunities for men and women to receive education and empowerment, but women still experience obstacles in becoming leaders. The author responds to this problem by analyzing the Korean drama